INTEGRAÇÃO DA PRODUÇÃO PELA PERSPECTIVA ORGANIZACIONAL - Oliveira, Ana Beatriz; Giacaglia, Marcelo Eduardo (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
Integration of the production process is considered a strong instrument to enhance quality and effectiveness in the construction industry and comprises three approaches: contractual, information processing technology and organizational. Even though recent literature stress the necessity of applying all three to achieve integration, a strong organizational approach can compensate for the lesser or absence of the others. The aim of this research is to analyze the presence of organizational integration features in success cases in the construction industry. The assessment considered two cases: one without the use of BIM, which represents the technological approach; and the other with a traditional contractual approach. The first was represented by the works of João Filgueiras Lima (Lelé) and Prouvé and the other by a case study of the production of a series of buildings of a self-storage company.